CORE VALUE DALAM BUDAYA ORGANISASI RABBANI - Tita Melia Milyane; Siti Syarah; Windi Ayu (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
The development of the fashion world is now reaching an impressive point, supported by the advancement of information technology that broadens knowledge about various kinds of fashion. Especially Muslim fashion trends are characterized by the development of the